Mutational spectrum of COH1 and clinical heterogeneity in Cohen syndrome. Issue 5 (28th April 2006) - Seifert, W; Holder-Espinasse, M; Spranger, S; Hoeltzenbein, M; Rossier, E; Dollfus, H; Lacombe, D; Verloes, A; Chrzanowska, K H; Maegawa, G H B; Chitayat, D; Kotzot, D; et al.
Abstract : Cohen syndrome (CS) is an autosomal recessive disorder with variability in the clinical manifestations, characterised by mental retardation, postnatal microcephaly, facial dysmorphism, pigmentary retinopathy, myopia, and intermittent neutropenia. Mutations in the gene COH1 have been found in an ethnically diverse series of patients. Brief clinical descriptions of 24 patients with CS are provided. The patients were from 16 families of different ethnic backgrounds and between 2.5 and 60 years of age at assessment. DNA samples from all patients were analysed for mutations in COH1 by direct sequencing. Splice site mutations were characterised using reverse transcriptase PCR analysis from total RNA samples. In this series, we detected 25 different COH1 mutations; 19 of these were novel, including 9 nonsense mutations, 8 frameshift mutations, 4 verified splice site mutations, 3 larger in frame deletions, and 1 missense mutation. We observed marked variability of developmental and growth parameters. The typical facial gestalt was seen in 23/24 patients. Early onset progressive myopia was present in all the patients older than 5 years. Widespread pigmentary retinopathy was found in 12/14 patients assessed over 5 years of age. We present evidence for extended allelic heterogeneity of CS, with the vast majority of mutations leading to premature termination codons in COH1 . Our data confirm the broad clinical spectrum of CS with some patients lacking even the characteristic facial gestalt and pigmentary retinopathy at school age.